Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Para resolver la ecuación cuadrática [tex]\(x^2 + 7x + 12 = 0\)[/tex] utilizando la fórmula general, vamos a seguir los siguientes pasos detallados:
1. Identificar los coeficientes de la ecuación cuadrática [tex]\(ax^2 + bx + c = 0\)[/tex]:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 7 \)[/tex]
- [tex]\( c = 12 \)[/tex]
2. Calcular el discriminante ([tex]\(\Delta\)[/tex]) que se usa en la fórmula cuadrática:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Sustituyendo los valores:
[tex]\[ \Delta = 7^2 - 4 \cdot 1 \cdot 12 = 49 - 48 = 1 \][/tex]
3. Aplicar la fórmula general, que es:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Dado que [tex]\(\Delta = 1\)[/tex], la raíz cuadrada de [tex]\(\Delta\)[/tex] es:
[tex]\[ \sqrt{1} = 1 \][/tex]
Ahora, sustituimos estos valores en la fórmula:
Para la primera raíz ([tex]\(x_1\)[/tex]):
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} = \frac{-7 + 1}{2 \cdot 1} = \frac{-6}{2} = -3 \][/tex]
Para la segunda raíz ([tex]\(x_2\)[/tex]):
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{-7 - 1}{2 \cdot 1} = \frac{-8}{2} = -4 \][/tex]
Por lo tanto, las soluciones de la ecuación [tex]\(x^2 + 7x + 12 = 0\)[/tex] son [tex]\(x_1 = -3\)[/tex] y [tex]\(x_2 = -4\)[/tex]. La respuesta correcta es:
A. [tex]\( x_1 = -3; x_2 = -4 \)[/tex]
1. Identificar los coeficientes de la ecuación cuadrática [tex]\(ax^2 + bx + c = 0\)[/tex]:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 7 \)[/tex]
- [tex]\( c = 12 \)[/tex]
2. Calcular el discriminante ([tex]\(\Delta\)[/tex]) que se usa en la fórmula cuadrática:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Sustituyendo los valores:
[tex]\[ \Delta = 7^2 - 4 \cdot 1 \cdot 12 = 49 - 48 = 1 \][/tex]
3. Aplicar la fórmula general, que es:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Dado que [tex]\(\Delta = 1\)[/tex], la raíz cuadrada de [tex]\(\Delta\)[/tex] es:
[tex]\[ \sqrt{1} = 1 \][/tex]
Ahora, sustituimos estos valores en la fórmula:
Para la primera raíz ([tex]\(x_1\)[/tex]):
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} = \frac{-7 + 1}{2 \cdot 1} = \frac{-6}{2} = -3 \][/tex]
Para la segunda raíz ([tex]\(x_2\)[/tex]):
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{-7 - 1}{2 \cdot 1} = \frac{-8}{2} = -4 \][/tex]
Por lo tanto, las soluciones de la ecuación [tex]\(x^2 + 7x + 12 = 0\)[/tex] son [tex]\(x_1 = -3\)[/tex] y [tex]\(x_2 = -4\)[/tex]. La respuesta correcta es:
A. [tex]\( x_1 = -3; x_2 = -4 \)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.